ADAPTATION OF BRASSICA NAPUS SEEDLINGS TO VARIOUS BIOTIC AND ABIOTIC STRESSES UNDER DARK AND LIGHT REGIMEN - Fawad Ali1, Farhad Ali1*, Ibtisam M. Alsudays2, Siham M.AL-Balawi3, Zahid Khorshid Abbas 3 Muneera A. Saleh4, Roobaea Alroobaea5, Muhammad Junaid Yousaf6 (Chelonian Research Foundation, 2024)
Roots of the plants are highly sensitive to interaction with abiotic or biotic components of the soil environment. During current study, 7 days old seedlings of hydroponically grown B. Napus were exposed to different biotic and abiotic stresses including AgNO3, Cinnamic acid, and Pseudomonas syringae under light and dark regimes. Also, the effect of different concentrations of nutrients was analysed by growing the B. Napus seedlings in 1 X, 0.5 X, 0.25 X of Hoagland solution. Data of root exudation of secondary metabolites with to respect to growth rate was noted for each treatment at the end of the week for each abiotic and biotic stress under dark and light at 24, 48 and 72 hours. It was noted that roots of dark grown seedlings exuded remarkably higher quantities of IAA and phenolics as compared to the control. Contrary to this, light exposure reduced the exudation of these secondary metabolites by B. Napus seedlings. Silver nitrate antagonistically affect the seedlings in dark due to the inhibition of the level of IAA, phenolics along with flavonoids and significantly reduced the growth rate. However, under the effect of 200mM cinnamic acid, the growth rate of seedling was improved with the inhibition of secondary metabolites in light condition. Interestingly, exudation of phytoalexins was not influenced conditions of light or dark while silver nitrate reduced its exudation from root in light. In the presence of CA, the light factor became an important modulator of phytoalexins exudation showing contrasting response. As expected, greater availability of nutrients(1 X Hoagland solution) positively influenced the release of secondary metabolites by roots. The effect of 200Mm of AgNO3 and P. syringae was adverse on B. Napus as both inhibited the level of overall exudation of flavonoids and phytoalexins in dark grown seedlings.